Analisis Pengaruh Pemecahan Saham (Stock Split) Terhadap Likuiditas Saham Dan Return Saham (Study Kasus Pada Perusahaan Yang Terdaftar BEI Periode 2007-2011) - Wijanarko, Iguh; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2012)
The increase in stock prices that are too high that influence the demand for or purchases of shares decreases, which in it make the share price does not fluctuate. For it does not happen then the company take action with the aim of lowering the price of shares on the stock price range of interest to prospective investors and the stock price can be reached by performing the split shares (stock split). Research on stock splits often enough, but give different results, it is necessary to do further research. The study was conducted on 31 companies that are listed on the Stock Exchange and they do stock split in the yearÂ  2007-2011. This study uses statistical analysis test two different test average with a 10-day observation period is t = -5 (5 days before stock split) and t = 5 (5 days after stock split ). The method of determination of sample using purposive sampling Base on the test results of one sample t test showed that the market reacts quickly seen from abnormal return with a significance level of 0.003 on the first day after the stock split and a significance level of 0.001 for the trading volume activity. While based on different test results showed no difference in abnormal return before and after the stock split with a significant level of 0.582, but showed differences in the trading volume activity with a significant level of 0.027.